Assessment of human milk samples obtained pre and post-influenza vaccination reveals a poor boosting of seasonally-relevant, hemagglutinin-specific antibodies - Yang, Xiaoqi; DeCarlo, Claire; Fox, Alisa; Pineda, Nicole; Powell, Rebecca L. R. (Frontiers in Immunology, 2023)
Introduction Influenza (flu) vaccination prevented over 100,000 hospitalizations and 7000 deaths from flu over the 2019-2020 season in the USA. Infants <6 months are the most likely to die from flu, though flu vaccines are only licensed for infants >6 months old. Therefore, it is recommended that flu vaccination occur during pregnancy, as this reduces severe complications; however, vaccination rates are suboptimal, and vaccination is also recommended postpartum. For breast/chest-fed infants, the vaccine is believed to elicit protective and robust seasonally-specific milk antibody (Ab). Few comprehensive studies exist examining Ab responses in milk after vaccination, with none measuring secretory Ab (sAb). Determining whether sAbs are elicited is critical, as this Ab class is highly stable in milk and mucosae. Methods In the present study, our aim was to determine to what extent specific Ab titers in the milk of lactating people were boosted after seasonal influenza vaccination. Over the 2019-2020 and 2020-2021 seasons, milk was obtained pre- and post-vaccination and assessed for specific IgA, IgG, and sAb against relevant hemagglutinin (HA) antigens by a Luminex immunoassay. Results IgA and sAb were not found to be significantly boosted, while only IgG titers against B/Phuket/3073/2013, included in vaccines since 2015, exhibited an increase. Across the 7 immunogens examined, as many as 54% of samples exhibited no sAb boost. No significant differences for IgA, sAb, or IgG boosting were measured between seasonally-matched versus mismatched milk groups, indicating boosting was not seasonally-specific. No correlations between IgA and sAb increases were found for 6/8 HA antigens. No boost in IgG- or IgA-mediated neutralization post vaccination was observed. Discussion This study highlights the critical need to redesign influenza vaccines with the lactating population in mind, wherein the aim should be to elicit a potent seasonally-specific sAb response in milk. As such, this population must be included in clinical studies.